The Administrative Felds of The Aylul Revolution Between (1961-1970) - Azad Ubed Salh; Ali Rasu Omer (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
The Aylul revolution between 1961/1970 in the modern history of Kurds is considered as one of the most important historical events for striving against achieving national rights which included a wide geographical area from Zakho to Khanaqin. In fact, Aylul revolution was not only an armed revolution, but also was movement of defacto governments in southern Kurdistan, because the revolution in the liberated areas of southern Kurdistan, apart from the headquarters of the Peshmerga forces, other institutions such as courts, schools, hospitals, newspapersandradi.Etc. have played a significant role in solving problems, spreading awareness and conveying the message of revolution inside and outside the country, which was a good response to say that kurds can govern themselves as a living nation. Our study consists of two axes: the first axis is the administrative boundary of the liberated areas of southern Kurdistan, and the second axis is how to manage the liberated areas.